Quarterly Report of the Justice Studies Center of the Americas: April - June 2005 - (:unkn) unknown (My University, 2016)
During the period, Chile’s Ministry of Justice hired JSCA to perform an “Empirical Evaluation of the Criminal Procedure Reform” in order to evaluate the process in view of the reform’s entry into force in Santiago. Also during this period, a delegation of Haitian judges visited Chile in order to attend lectures on “Chile’s Criminal Procedure Reform” and participate in related activities. The XII Meeting of the JSCA Board of Directors was held on June 20, 2005 in Kingston, Jamaica.